PERAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM MENJALANKAN PROGRAM SATUAN PENDIDIKAN AMAN BENCANA (STUDI KASUS BPBD KABUPATEN BANTUL) - Rifaldi; Suharni, Cici; Palasara Brahmani Laras; Ficky Adi Kurniawan (Indonesian Journal of Environment and Disaster, 2023)
This article has a focus on the role of the Regional Disaster Management Agency in schools in carrying out the Disaster Safe Education Unit (SPAB) program with the case study BPBD Bantul Regency. This is because Indonesia is a country with a high level of natural disasters because it is at the confluence of various earth plates. Meanwhile school is the second place for students to seek and gain knowledge after being at home, especially in studying potential disasters that can occur in the environment where they live. It should be noted that in 2006 an earthquake with a magnitude of 5.9 occurred in Bantul Regency which resulted in fatalities and heavy losses, including educational facilities. The purpose of this study is to find out how the role of BPBD Bantul Regency in disaster management in schools so far and to know and see how the Disaster Safe Education Unit program in Bantul Regency is running. The method used in this research is descriptive qualitative. The results obtained are that the BPBD within the scope of the school plays a role in educating children to have a more disaster preparedness attitude, helping facilitate school needs, and introducing disaster education from an early age. The SPAB program is carried out to build resilience in dealing with disasters by school members, one of whose efforts is to provide material about disasters. BPBD encourages schools in Bantul Regency to incorporate disaster material into their learning and extracurricular.